El seguro social campesino en la ley de seguridad social - Collaguazo Pilco, Rodrigo (2017)
This research aims at highlighting the vulnerability of the rights of which the object of the peasants of Ecuador, which has the weight of having a Constitution in which they are recognized as a State of rights and Justice; this is not applied in the sector Rural Ecuadorian. In terms of rights the peasantry has gradually conquered them, so that access to land, water, education, health, among others is a sector that are economically, socially and politically empowered, however today. Constitution, one of them is the right to Social Security and within this right to peasant social insurance. The Social Security Farmer, started in August 1968 and is classified as a unique insurance in Latin America and unique questionnaire in the world for its particular characteristics, one of them is that they have no dependency relationship, their character is family community, Intercultural and that according to international studies is low, cost efficient, broad coverage and great empowerment of the beneficiaries. In 1998, in the Constitution drafted and approved in the social insurance peasant acquired constitutional rank, that is, ceased to be guaranteed only by law, and is guaranteed by the Constitution, which in addition to guaranteeing the right to social security of peasants It was also extended to the artisanal fisherman, that is to say, it involves the fundamental actors of the food of the Ecuadorians, doing justice to those who make the effort both in the field and at sea. With this entire new normative framework, the peasant social insurance manages to increase its coverage, as well as its benefits. With the Constitution of 2008, it is known by all that the Social Security in the rural sector is channeled through the Rural Social Security, which is a special insurance of Universal Obligatory Insurance and is also part of the Ecuadorian Social Security Institute. However, the coverage, the weight of the charter raises that compulsory universal insurance will extend to the entire urban and rural population regardless of their employment relationship and that peasant social insurance will protect the rural population, this is not being met Y What is safer is the right to social security of the peasantry as citizens and organizations have the right. A separate question but it is necessary to point out that as in any other space it is where individual rights and collective rights come together and coexist. Regarding the vulnerability of the peasants' rights to Social Security, it should be pointed out that currently the IESS, the affiliation of new members of the rural sector is not allowed because they are covered by the social security law, specifically article 129, Which states that the incorporation of new affiliates and beneficiaries should be directly related to the growth of the number of members to compulsory general insurance. That is clearly unconstitutional and therefore violates rights guaranteed by the Constitution. Access to a right that has a citizen or collective, and which is guaranteed by the Constitution cannot be hindered and less denied by access or not to other people to social security law. Being more pragmatic men and women in the rural sector cannot wait for other people to join the general insurance and at that time concrete their right to social security, therefore the rights is direct and immediate application, therefore cannot have an intermediary or any conditionality In this context, it is argued that the right to security must be directly applicable and therefore it is necessary to reform the social security law to guarantee the right of the rural sector, collectively and individually.